2017
DOI: 10.1016/j.placenta.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Hormone dependent uterine epithelial-stromal communication for pregnancy support

Abstract: Human fertility is a relatively inefficient process. Despite the presence of visibly healthy embryos, 30% of pregnancies generated by assisted reproductive technology (ART) fail before the second trimester. The uterine microenvironment plays a critical role in establishing and maintaining a successful pregnancy that requires coordinated communication between the epithelial and stromal cells of the endometrium. The epithelial cells must cease proliferation and become permissive for the conceptus (embryo and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 100 publications
0
33
0
2
Order By: Relevance
“…Another factor that modified the dendritic spine number is hormones (for review see Frankfurt & Luine, ). During pregnancy, estrogen and progesterone in high levels are present (for review see Berkane et al, ; Frankfurt & Luine, ; Wang, Wu, & DeMayo, ) In addition, these two hormones also exhibited a neuroprotective effect on the PFC and hippocampus (for review see Frankfurt & Luine, ). Accordingly, the hippocampus has high levels of estrogen receptors, which may have a critical role in the estrous cycle and pregnancy (for review see Frankfurt & Luine, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that modified the dendritic spine number is hormones (for review see Frankfurt & Luine, ). During pregnancy, estrogen and progesterone in high levels are present (for review see Berkane et al, ; Frankfurt & Luine, ; Wang, Wu, & DeMayo, ) In addition, these two hormones also exhibited a neuroprotective effect on the PFC and hippocampus (for review see Frankfurt & Luine, ). Accordingly, the hippocampus has high levels of estrogen receptors, which may have a critical role in the estrous cycle and pregnancy (for review see Frankfurt & Luine, ).…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis of caprine, ovine and bovine FOXL2 promoter sequences confirmed the presence of a PRE motif that suggests regulation of FOXL2 gene expression by P4 [68,69]. The association of P4 with PGR affects the expression of numerous transcription factors, including FOXO1, HOXA10 or HAND2 [38], which are involved in cell differentiation and secretory protein production in the uterus [70]. The interaction between P4 and FOXL2 expression was further evidenced using a COS7 cell line overexpressing PGR protein where P4 supplementation activated the FOXL2 promoter.…”
Section: Discussionmentioning
confidence: 78%
“…The biological actions of E2 and P4 are mainly mediated by their nuclear receptors, Estrogen Receptor (ESR1-2, formerly named ERα-β, transcribed from two distinct genes) and Progesterone nuclear Receptor (PGRA-B, two isoforms from the same gene; [15,35]), respectively. Upon binding with E2 or P4, the receptors translocate to the nucleus and modulate expression of E2 or P4 target genes [15,[35][36][37][38]. In the last decade, studies have identified direct target genes of ESR and PGR in humans, rodents and cattle [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGRB is a gene activator that is dependent on P4, whereas PGRA is a weak gene activator that acts as a potent inhibitor of PGRB, thereby reducing the effects of P4 (Pieber, Allport, & Bennett, 2001). ESR are transcribed from two genes: ESR1 and ESR2 (Wang, Wu, & DeMayo, 2017). Uterine receptivity to implantation is P4 dependent; however, implantation events are preceded by loss of gene expression of PGR and ESR1 by bovine uterine epithelia (Bazer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%